Margaret C. Flinn, editor. Drawing (in) the Feminine: Bande Dessinée and Women. The Ohio State University Press, 2024. - Ryan Gomez (Studies in 20th & 21st Century Literature, 2025)
Review of Margaret C. Flinn, editor. Drawing (in) the Feminine: Bande Dessinée and Women. The Ohio State University Press, 2024. xii + 263 pp.
Keywords: bande dessinée; French; francophone; comics; graphic novels; women; gender